Financial Sector Reforms and Economic Growth: Evidence from Nigeria - Olowofela, Enitan O.; Adebowale, Edward Adedoyin; Adejonwo, Ayoola Quadri (Binus Business Review, 2018)
This research analyzed the impact of financial reforms on economic growth in Nigeria. The scope of this research covered the period between1986â 2016.This period was chosen because liberalization of Nigeria financial sector began in 1986 with the introduction of Structural Adjustment Programme (SAP), which policy thrust included deregulation of interest rates. Secondary data were collected from Central Bank of Nigeria statistical bulletin and National Bureau of Statistics publications. This research used econometrics analysis. Ordinary Least Squares (OLS) technique and Cochrane Orcutt iterative method were used to analyze the data. The results show that implemented financial reforms during the period has positive impact on economic growth. This research recommends that government should enhance financial reforms and macroeconomic stability and be sensitive to the behavior of interest rates especially, lending rates for overall economic growth in the country.